2015
DOI: 10.1177/0895904815613443
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Assessment and English Language Learners With Disabilities

Abstract: This article highlights a set of principles and guidelines, developed by a diverse group of specialists in the field, for appropriately including English language learners (ELLs) with disabilities in large-scale assessments. ELLs with disabilities make up roughly 9% of the rapidly increasing ELL population nationwide. In spite of the small overall percentage of students that they represent, this group experiences significant learning and assessment challenges. In the context of successfully educating all stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Compared to the literature on accessibility features in content assessments, research on such tools in ELP assessments is limited. In a meta-analysis, Liu et al (2020) found only 11 studies between 2010 and 2018 that were conducted on ELs and only a couple focused on ELP assessments. Existing studies focus on foreign language assessments in higher education rather than K-12 contexts (e.g., Choi & Cho, 2016;Frankenberg-Garcia, 2011).…”
Section: Previous Research On Universal Tools For Elsmentioning
confidence: 99%
“…Compared to the literature on accessibility features in content assessments, research on such tools in ELP assessments is limited. In a meta-analysis, Liu et al (2020) found only 11 studies between 2010 and 2018 that were conducted on ELs and only a couple focused on ELP assessments. Existing studies focus on foreign language assessments in higher education rather than K-12 contexts (e.g., Choi & Cho, 2016;Frankenberg-Garcia, 2011).…”
Section: Previous Research On Universal Tools For Elsmentioning
confidence: 99%
“…After recognizing that ELs had some distinct linguistic needs, states soon changed their accommodations policies for ELs to focus on linguistic accommodations, such as native language translation of directions and bilingual dictionaries and glossaries (Thurlow, 2014). These shifts had important implications for ELs with disabilities, often the most ignored of all students in terms of inclusion in large-scale assessments (Liu, Ward, Thurlow, & Christensen, 2017; Thurlow, Albus, Liu, & Rivera, 2006; Thurlow, Barrera, & Zamora-Duran, 2006). The first paradigm shift changed the way that education systems assessed their students with disabilities, also paving the way for educators, researchers, and parents to make assessments more accessible for ELs.…”
Section: First Paradigm Shift: Inclusion In Standards-based Assessmenmentioning
confidence: 99%
“…It is relatively recently that ELs with disabilities have been considered in relation to assessment accessibility and accommodations. Only in the past couple of years has policy (e.g., Albus & Thurlow, 2007) and practice (e.g., Albus & Thurlow, 2013; Liu et al, 2013) been examined for these students, who too often in the past were simply exempted from testing. Research related to including these students in assessments is just beginning, and much of it is policy research (e.g., Christensen, Albus, Liu, Thurlow, & Kincaid, 2013; Thurlow, Liu, Ward, & Christensen, 2013).…”
Section: Accessibility and Accommodations Considerations For Els Withmentioning
confidence: 99%